"A step away from complacent knowing": Reinvigorating democracy through the humanities. (July 2015) - Musil, Caryn McTighe
"A step away from complacent knowing" argues that the humanities have long been understood as enhancing civic life and human intellectual and moral development. At moments when democratic societies seem at risk, however, such as the birth of the new US Republic, the aftermath of World War II, and in the face of an anemic twenty-first-century American democracy, the humanities have been deployed with special urgency to cultivate democratic values and practices. The 2012 report, A Crucible Moment: College Learning and Democracy's Future, underscores how central the humanities are in such a stratified, diverse, and globally linked world. The report both cited and launched a vibrant creativity within the academy. Civically enriched, student-centered humanities designs illuminate a path for reinvigorating democracy while also rejuvenating the humanities themselves.